Pre-trial disposal: the effectiveness of the National Legal Aid Foundation in safeguarding the rights of arrested and detained persons / Collin Arvind Andrew - Collin Arvind, Andrew (2015)
It was revealed in Parliament in November 2009 that accused persons were unrepresented in 84,376 out of 108,528 criminal trials that took place in the Magistrate courts in 2008. Then Chairman of the Bar Council stated that there were more than 90% of persons remanded who were without any legal representation. A vast majority of them do not have the financial means to engage a lawyer and those who can afford a lawyer are usually not able to represent them until after they are charged in Court as there is the issue of access to justice at the pre-trial stage. Past literature would show that the rights afforded to an arrested/detained person especially pertaining to the right to counsels are reduced. The reason many people go unrepresented is because there exists a large number of people who do not receive legal assistance from the two main providers of legal aid in Malaysia i.e. the Government legal aid departments and the Bar Council Legal Aid Centres. In view of the aforesaid, the National Legal Aid Foundation has been set up to plug this gap.